2005
DOI: 10.1107/s1600536805039565
|View full text |Cite
|
Sign up to set email alerts
|

4′-(4-Methylbenzoyl)-1′-methyldispiro[indole-3(2H),2′-pyrrolidine-3′,3′′(2′′H)-indole]-2,2′′-dione

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.003 Å R factor = 0.051 wR factor = 0.135 Data-to-parameter ratio = 12.9For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The crystal structures of several biologically significant monospiropyrrolidines (Chandralekha et al, 2014) and dispiropyrrolidines (Palani et al, 2006) have been reported in the literature, but only few reports are available on the crystal structure of trispiropyrrolidines. In continuation of our work in this field, the crystal structure of title trispiropyrrolidine is reported on herein.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The crystal structures of several biologically significant monospiropyrrolidines (Chandralekha et al, 2014) and dispiropyrrolidines (Palani et al, 2006) have been reported in the literature, but only few reports are available on the crystal structure of trispiropyrrolidines. In continuation of our work in this field, the crystal structure of title trispiropyrrolidine is reported on herein.…”
Section: Chemical Contextmentioning
confidence: 99%